Kerkia Radoman, 1978 (Caenogastropoda: Hydrobiidae): endemism, apparently morphostatic evolution and cryptic speciation. (2nd October 2022) - Hofman, Sebastian; Grego, Jozef; Beran, Luboš; Jaszczyńska, Aleksandra; Osikowski, Artur; Falniowski, Andrzej
ABSTRACT: Kerkia is a snail genus inhabiting mainly subterranean waters. Live specimens of Kerkia were collected in the West Balkans. Mitochondrial cytochrome c oxidase subunit I and nuclear histone H3 were sequenced. Populations of Kerkia molecularly represented 10 mOTUs, each deserving a species rank. Apart from known species, five new species are described. The interspecies differences in shell morphology were slight and thus morphology did not reflect the evident molecular differences. All available information about the penes and female reproductive organs are summarised and their limited usefulness in species-level taxonomy is discussed. Kerkia seems to represent another example of morphostatic evolution, a result of non-adaptive radiation marked by the rapid proliferation of sibling species, whose ecology most probably remains the same. In Kerkia, intrapopulation genetic diversity does not (or almost does not) exist, and the same is true for intraspecies variation. At the same time, there is a high level of molecular difference between the species. Despite potential means for range expansion of the stygobiont fauna provided by interstitial habitats, which reduce the levels of endemism in some stygobiont gastropod species, the species of stygobiont Kerkia are restricted to small geographic areas. LSID: urn:lsid:zoobank.org:pub:F710D90A-4427-4C64-AAFE-5ADE89EEAABC